Study on the Driving Force of the Subjects of Environmental Public Interest Litigation in China: The Impact of Current Laws and Regulations on Social Organisations’ Participation in Environmental Public Interest Litigation as an Example - Zou, Rongsheng (International Journal of Social Sciences and Public Administration, 2024)
In order to follow China’s basic national policy of "protecting the environment", stimulate the supervision function of multiple subjects, and avoid the occurrence of "government failure", China has stipulated that social organisations can initiate environmental public interest litigation, which adds bricks and mortar to China’s environmental protection cause. However, due to the complexity of the real situation, China’s current laws and regulations in stimulating the vitality of social organisations are flawed, social organisations have lost their due function, in order to stimulate the driving force of social organisations, to improve the system to put forward a good strategy, this paper will be compared with the United States and China to put forward the system of our country can be borrowed from, the reality of the dilemma of the proposed measures to cope with it.